Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Whole-transcriptome profiling reveals the landscape of host circular RNAs during grass carp reovirus infection - Tian Bu; Dongmei Zhong; Fang Gou; Yinggang Li; Siwan Xu; Yifei Wang; Jinwang Ding; Rong Yang; Shaojun Liu (Aquaculture, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

AO168=O at environmentally relevant concentrations induces reproductive toxicity by causing germline apoptosis and cell cycle arrest in Caenorhabditis elegans - Yuxing Wang; Luyao Gu; Simin Li; Ru Liu; Tong Meng; Yue Yu; Rong Ye; Houhu Zhang; Rong Zhou; Yuanqing Bu (Environmental Research, 2025)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Oxalic acid–modified activated carbons under hydrothermal condition for the adsorption of the 2-butanone - Naijing Bu; Xiaomeng Liu; Tianzhen Li; Rong Li; Qiang Zhen (Environmental Science and Pollution Research, 2023)

Exploration for cobalt/nitrogen-doped catalyst to creatinine degradation via peroxymonosulfate activation: toxicity evaluation, statistical modeling, and mechanisms study - Jiadi Liu; Yawen Dong; Yu Kang; Qian Kong; Kuaibing Wang; Feifei Mao; Yuanqing Bu; Rong Zhou; Chunyong Zhang; Hua Wu (Environmental Science and Pollution Research, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Petal-like hierarchical Co3O4/N-doped porous carbon derived from Co-MOF for enhanced peroxymonosulfate activation to remove tetracycline hydrochloride - Qingqing Li; Zhujuan Ren; Yutong Liu; Chibin Zhang; Jiadi Liu; Rong Zhou; Yuanqing Bu; Feifei Mao; Hua Wu (Chemical Engineering Journal, 2023)

Effects of Chemotherapy on Neuroinflammation, Neuronal Damage, Neurogenesis, and Behavioral Performance in Bone Marrow Transplantation Recipient Mice - Zhong-Yuan Yu; Man-Yu Xu; Zhi-Hao Liu; Gui-Hua Zeng; Huan Fan; Cheng-Rong Tan; Yun-Feng Tu; Xian-Le Bu; Yan-Jiang Wang (Neurotoxicity Research, 2022)

Different leaf carbon, nitrogen, and phosphorus stoichiometry and carbon and nitrogen isotopes among peatland plants in northeastern China - Chong-Juan Chen; Xue-Yan Liu; Xian-Wei Wang; Chao-Chen Hu; Shi-Qi Xu; Rong Mao; Zhao-Jun Bu; Yun-Ting Fang; Keisuke Koba (Plant and Soil, 2021)

Autophagic Modulation by Trehalose Reduces Accumulation of TDP-43 in a Cell Model of Amyotrophic Lateral Sclerosis via TFEB Activation - Ying Wang; Feng-Tao Liu; Yi-Xuan Wang; Rong-Yuan Guan; Chen Chen; Da-Ke Li; Lu-Lu Bu; Jie Song; Yu-Jie Yang; Yi Dong; Yan Chen; Jian Wang (Neurotoxicity Research, 2018)

MiR-219 Protects Against Seizure in the Kainic Acid Model of Epilepsy - Honghua Zheng; Rong Tang; Yi Yao; Zhilin Ji; Yuanyuan Cao; Zhaoji Liu; Feng Peng; Wenjie Wang; Dan Can; Huiqin Xing; Guojun Bu; Huaxi Xu; et al. (Molecular Neurobiology, 2016)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

Shift in abundance and structure of soil ammonia-oxidizing bacteria and archaea communities associated with four typical forest vegetations in subtropical region - Yong-Chun Li; Bu-Rong Liu; Song-Hao Li; Hua Qin; Wei-Jun Fu; Qiu-Fang Xu (Journal of Soils and Sediments, 2014)